Tropical numerical weather prediction studies for the 1987 Australian summer monsoon (MAUSAM, 1990)
The performance of the ECMWF analysis-forecast system in depicting the main feature of the 1987 Australian monsoon is described. The features include the mean circulation for the period and the onset and active/break periods of the monsoon. The model is successful in predicting the mean feature up to 3 days ahead with the main deficiency being the marked weakening of the upper level divergent circulation with time.  The analyses successfully depict most features of the monsoon circulation. Although the model is able to forecast onset up to about 1 day ahead and the subsequent episodes up to about 2 days ahead, there is a tendency in the model forecasts to weaken the low level westerly winds with time.